1989
DOI: 10.1002/pi.4980210209
|View full text |Cite
|
Sign up to set email alerts
|

XPS and SEM study of UV laser surface modification of polymers

Abstract: Several commercial polymers—poly(ethylene) (PE), poly(propylene) (PP), poly(vinylidene fluoride) (PVF2), poly(vinyl chloride) (PVC) and polystyrene (PS)—were treated in air with an argon‐fluorine UV excimer laser (λ = 193 nm). The polymer etch rate was investigated by two methods: quartz crystal microbalance (QCM) and piercing of films. X‐ray photoelectron spectroscopy (XPS) analysis was performed on the modified surfaces after laser exposure at various fluences. Samples were subsequently analysed by scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Then the phenyl and aminyl radicals created inside the polymer matrix can combine or lead to crosslinking or branching of the polymer, as shown for cross-linking in steps 4 and 5 of Scheme 6. It was suggested that cross-linking will lead to a peak broadening in the XPS spectra [155]. We also detected some broadening of the peaks after irradiation and found some insoluble residues for thick films, indicating a polymer network.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Then the phenyl and aminyl radicals created inside the polymer matrix can combine or lead to crosslinking or branching of the polymer, as shown for cross-linking in steps 4 and 5 of Scheme 6. It was suggested that cross-linking will lead to a peak broadening in the XPS spectra [155]. We also detected some broadening of the peaks after irradiation and found some insoluble residues for thick films, indicating a polymer network.…”
Section: Discussionmentioning
confidence: 83%
“…A spectrum of a SiC disk was used as background. The difference spectra of the SiC disk after irradiation with the highest fluence applied in this study (155 mJ cm 2 ) were measured after various pulse numbers (50, 100, 500, and 5,000) and at the highest repetition rate (10 Hz). No changes in the spectra were observed, suggesting that SiC is stable under the applied conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the morphology of the treated surfaces is significantly changed by the creation of many small wrinkles (Figure 7(c)). Some wrinkles were developed into microholes, indicating the violent degradation of one of the material inorganic additives (Figure 7(c)) [33]. Other SEM observations showed that these microholes increase in size and number with higher durations of UV/ozone treatment.…”
Section: Energetic Treatmentsmentioning
confidence: 94%
“…Therefore, nanoscale characterization of the surfaces of dialysis membrane sterilized by γ irradiation should be performed to facilitate preparation of dialysis membranes with superior biocompatibility. Although electron microscopy (EM)16 and XPS17 are representative methods for nanoscale characterization of material surfaces, these methods require high vacuum conditions and various pretreatments like vapor deposition to allow surface nanoscale surface characterization 18–19. However, atomic force microscopy (AFM) can be used for nanoscale evaluation of surface properties under wet conditions without complicated pretreatments 20–21.…”
Section: Introductionmentioning
confidence: 99%